Engineered chimeras reveal the structural basis of hexacoordination in globins: A case study of neuroglobin and myoglobin - Boron, Carlos Ignacio (2014)
Background Myoglobin (Mb) and neuroglobin (Ngb) are representative members of pentacoordinated and bis-histidyl, hexacoordinated globins. In spite of their low sequence identity, they show surprisingly similar three-dimensional folds. The ability of Ngb to form a hexacoordinated bis-histidyl complex with the distal HisE7 has a strong impact on ligand affinity. The factors governing such different behaviors have not been completely understood yet, even though they are extremely relevant to establish structure-function relationships within the globin superfamily.